Pengaruh Pengalaman Dan Kepuasan Terhadap Loyalitas Pelanggan Di Mie Gacoan Ponorogo - Rizka Amalia; Maulida Nurhidayati (Niqosiya: Journal of Economics and Business Research, 2023)
This study aims to test and determine the effect of experience and satisfaction on customer loyalty in Ponorogo gacoan noodles partially or simultaneously. This study uses a quantitative research design. In this study researchers used a questionnaire in collecting data. Meanwhile, to find out the number of samples, the researchers used the Cochran formula calculation and used incidental sampling techniques. In processing and analyzing data, researchers used the classical assumption test, multiple linear regression test, R^2 test, and hypothesis testing (t test and F test). The results of this study indicate that customer experience has a significant effect on customer loyalty at Mie Gacoan Ponorogo, customer satisfaction has a significant effect on customer loyalty at Mie Gacoan Ponorogo and simultaneously customer experience, and customer satisfaction has a significant effect on loyalty at Mie Gacoan Ponorogo. The magnitude of the influence exerted by the variables of customer experience and customer satisfaction on customer loyalty is 53.4%.